A novel method to determine the flow accelerated corrosion rate in the elbow. Issue 6 (11th January 2012) - Zhu, X. L.; Lu, X. F.; Ling, X.
Abstract Flow‐accelerated corrosion (FAC) is the most common failure in nuclear power plants. The FAC rate conforms to the experimental results in lab, which are calculated by some other FAC rate prediction models. However, when these models are employed to calculate the FAC rate of the elbow, the result is opposite to actual situation of failure of the elbow. In this paper, a new prediction model is proposed to calculate the flow accelerated corrosion (FAC) rate in the elbow, which combine the steady‐state mass transfer model of electrochemical theory and one‐dimensional galvanic corrosion model. Firstly, the distribution of velocity in the elbow is counted by FLUENT. Secondly, the free corrosion potential and the free corrosion current density are calculated by steady‐state mass transfer model. At last, the novel model is used to obtain the FAC rate of the elbow. The result will show that the FAC rate of the outward bend of the elbow is two‐orders than the inward bend of the elbow. The outward bend of elbow is the defective position, which accords with the statistical result of Kuen Ting et al.